Perturbed bone composition and integrity with disorganized osteoblast function in zinc receptor/Gpr39‐deficient mice. Issue 5 (2nd January 2018) - Jovanovic, Milena; Schmidt, Felix N.; Guterman‐Ram, Gali; Khayyeri, Hanifeh; Hiram‐Bab, Sahar; Orenbuch, Ayelet; Katchkovsky, Svetlana; Aflalo, Anastasia; Isaksson, Hanna; Busse, Björn; Jähn, Katharina; Levaot, Noam
Abstract : Changes in bone matrix composition are frequently found with bone diseases and maybe associated with increased fracture risk. Bone is rich in the trace element zinc. Zinc was established to play a significant role in the growth, development, and maintenance of healthy bones; however, the mechanisms underlying zinc effects on the integrity of the skeleton are poorly understood. Here, we show that the zinc receptor (ZnR)/Gpr39 is required for normal bone matrix deposition by osteoblasts. Initial analysis showed that Gpr39‐deficient ( Gpr39 −/− ) mice had weaker bones as a result of altered bone composition. Fourier transform infrared spectroscopy analysis showed high mineral‐to‐matrix ratios in the bones of Gpr39 −/− mice. Histologic analysis showed abnormally high numbers of active osteoblasts but normal osteoclast numbers on the surfaces of bones from Gpr39 −/− mice. Furthermore, Gpr39 −/− osteoblasts had disorganized matrix deposition in vitro with cultures exhibiting abnormally low collagen and high mineral contents, findings that demonstrate a cell‐intrinsic role for ZnR/Gpr39 in these cells. We show that both collagen synthesis and deposition by Gpr39 −/− osteoblasts are perturbed. Finally, the expression of the zinc transporter Zip13 and a disintegrin and metalloproteinase with thrombospondin motifs family of zinc‐dependent metalloproteases that regulate collagen processing was downregulated in Gpr39 −/− osteoblasts. Altogether, our results suggest that zinc sensing by ZnR/Gpr39 affects the expression levels of zinc‐dependent enzymes in osteoblasts and regulates collagen processing and deposition.—Jovanovic, M., Schmidt, F. N., Guterman‐Ram, G., Khayyeri, H., Hiram‐Bab, S., Orenbuch, A., Katchkovsky, S., Aflalo, A., Isaksson, H, Busse, B., Jahn, K., Levaot, N. Perturbed bone composition and integrity with disorganized osteoblast function in zinc receptor/Gpr39‐deficient mice. FASEB J. 32, 2507–2518 (2018). www.fasebj.org